2015
DOI: 10.1111/hpb.12379
|View full text |Cite
|
Sign up to set email alerts
|

Results of laparoscopic radiofrequency ablation for HCC. Could the location of the tumour influence a complete response to treatment? A single European centre experience

Abstract: LRFA of HCC is safe, feasible and achieves excellent results in selected patients. LRFA should be the first-line technique for subcapsular lesions as it minimizes the risk of tumoural seeding and improves ICR. Proximity to gallbladder interferes in treatment efficacy (lower rate of ICR and lower rate of SCR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 31 publications
2
31
1
Order By: Relevance
“…Furthermore, collected with the intention of examining a wide range of procedures, the NSQIP data set utilized does not code for some relevant disease‐specific characteristics such as disease stage, tumor size, number of lesions ablated histologic grade, or lymph node evaluation. Specific location of tumor within the liver is also not collected, which has been shown to be influential to long‐term outcomes in operative approach …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, collected with the intention of examining a wide range of procedures, the NSQIP data set utilized does not code for some relevant disease‐specific characteristics such as disease stage, tumor size, number of lesions ablated histologic grade, or lymph node evaluation. Specific location of tumor within the liver is also not collected, which has been shown to be influential to long‐term outcomes in operative approach …”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic approaches for thermal ablation provides access to difficult tumors, particularly if the tumors are located underneath the liver capsule, adjacent gallbladder, or diaphragm [18, 19]. In this study, we compared the efficacy, complication rates and long-term outcomes between laparoscopic MWA and RFA procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits associated with percutaneous ablation, there are sitll HCC cases that are not amenable to a direct percutaneous approach due to the location of the nodule, particularly if it is near the capsule or diaphragm [1518]. An alternative method of treating these nodules is to utilize a laparoscopic approach [19], which allows the physician to grossly examine the tumor spread, improve tumor staging via intra-operative ultrasound (IOUS) and identify safer insertion paths to treat tumors located in difficult location [2023].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison studies between laparoscopic and percutaneous ablations have shown that a laparoscopic approach is associated with a decreased rates of LTP in subcapsular tumors by allowing for more aggressive treatment without risk of burning adjacent organs, diaphragms and abdominal wall (10). As a result, select institutions have recommended laparoscopic ablations are the first-line treatment for patients with subcapsular liver tumors (68). …”
Section: Current Techniques For Treating Liver Cancer Using Microwavementioning
confidence: 99%